Is there still a role for abatacept in the treatment of lupus?. (September 2014) - Hoi, Alberta; Littlejohn, Geoff
<x xml:space="preserve">Abstract</x> Introduction: The quest for safer and more effective treatments for systemic lupus erythematosus (SLE) has led to the development of many new biologic therapies. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Vinorelbine&logicalOpe1=OR&field2=articletitle&text2=Vinorelbine&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Abatacept is the first drug targeting co-stimulation between T cells and antigen presenting cells, with abundant pre-clinical evidence to support its use in SLE. Areas covered: This review will present the relevant aspects of lupus pathophysiology pertaining to the mechanism of action of abatacept, a summary of murine studies and the latest human clinical trials. Expert opinion: Abatacept has demonstrated efficacy in both rheumatoid arthritis and psoriatic arthritis, and earlier studies have suggested tantalising evidence of efficacy in SLE. However, the latest randomised double-blinded study showed disappointingly negative results, much like the case of rituximab in SLE. Currently, abatacept remains a possible therapeutic option as an off-label therapy, and it is a part of our therapeutic armamentarium in difficult cases. The need to find appropriate definitions of response and optimal study design continues to be paramount in the field of lupus therapies.